2017
DOI: 10.1016/j.atmosenv.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Regional and hemispheric influences on temporal variability in baseline carbon monoxide and ozone over the Northeast US

Abstract: Interannual variability in baseline carbon monoxide (CO) and ozone (O), defined as mixing ratios under minimal influence of recent and local emissions, was studied for seven rural sites in the Northeast US over 2001 - 2010. Annual baseline CO exhibited statistically significant decreasing trends (-4.3 - -2.3 ppbv yr), while baseline O did not display trends at any site. In examining the data by season, wintertime and springtime baseline CO at the two highest sites (1.5 km and 2 km asl) did not experience signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Several studies have examined the interannual variability of CO by using 3‐D modeling or ground measurements like the ones provided by the National Oceanic and Atmospheric Administration (NOAA) Climate Monitoring and Diagnostics Laboratory (CMDL) air sampling network (e.g., Duncan & Logan, 2008; Novelli et al., 1998; Novelli et al., 1992; Wotawa et al., 2001; Y. Zhou et al., 2017). Our study builds on past works by using seasonally averaged tropospheric CO column from MERRA‐2 from 2014 – 2018 (Figure 3) to analyze the changes in CO specifically over eastern North America and the WNAO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the interannual variability of CO by using 3‐D modeling or ground measurements like the ones provided by the National Oceanic and Atmospheric Administration (NOAA) Climate Monitoring and Diagnostics Laboratory (CMDL) air sampling network (e.g., Duncan & Logan, 2008; Novelli et al., 1998; Novelli et al., 1992; Wotawa et al., 2001; Y. Zhou et al., 2017). Our study builds on past works by using seasonally averaged tropospheric CO column from MERRA‐2 from 2014 – 2018 (Figure 3) to analyze the changes in CO specifically over eastern North America and the WNAO.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have examined the interannual variability of CO by using 3-D modeling or ground measurements like the ones provided by the National Oceanic and Atmospheric Administration (NOAA) Climate Monitoring and Diagnostics Laboratory (CMDL) air sampling network (e.g., Duncan & Logan, 2008;Novelli et al, 1998;Novelli et al, 1992;Wotawa et al, 2001;Y. Zhou et al, 2017).…”
Section: Carbon Monoxidementioning
confidence: 99%
“…In order to obtain a best-fit solution using Eq. (4) for all the data, we regressed the numerator against the denominator using an ordinary least-squares (model 1) Y |X approach (Isobe et al,1990;Zobitz et al, 2006).…”
Section: Regression Plot Analysismentioning
confidence: 99%
“…S5). Zhou et al (2017) suggested that baseline CO in rural northeastern US areas was controlled by a multitude of factors, including global biomass emissions, large-scale circulation, and cyclone activity. At the Bronx site, the low percentile value, close to regional baseline levels, was possibly determined by a range of factors, whose importance could have varied from year to year.…”
Section: Relationships Between Gem and Anthropogenic Tracersmentioning
confidence: 99%